UPAYA KELUARGA DALAM PENGUATAN PENDIDIKAN AGAMA ISLAM BAGI ANAK REMAJA (SMP-SMA) DI RW 02 KELURAHAN MERJOSARI KOTA MALANG - Hilda Ulil Aidiyah Muhid; Nur Hasan; Khoirul Asfiyak (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
In the family the role of parents is very important. They are a model or reflection for their children. Therefore parents must familiarize, supervise, and foster Islamic religious education for their children. The purpose of this study is to describe the condition of Islamic religious education knowledge for adolescents (SMP-SMA) at RW 02, Merjosari Malang, to describe the efforts of families in providing Islamic education and to describe the obstacles faced by families in strengthening Islamic religious education for adolescents (SMP-SMA) at RW 02, Merjosari, Malang. The research approach used in this study is a descriptive qualitative approach. The data obtained came from interview scripts, photographs, personal documents and other official records. In this case the researcher acts as a full participant or full instrument. The results showed that the Family Efforts in Strengthening Islamic Religious Education for Adolescents (SMP-SMA) in RW 02, Merjosari Malang, were considered very good.